If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = -16 + 3x Reorder the terms: 2 + 6x = -16 + 3x Solving 2 + 6x = -16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 6x + -3x = -16 + 3x + -3x Combine like terms: 6x + -3x = 3x 2 + 3x = -16 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 3x = -16 + 0 2 + 3x = -16 Add '-2' to each side of the equation. 2 + -2 + 3x = -16 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -16 + -2 3x = -16 + -2 Combine like terms: -16 + -2 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 37=8-31u | | K^2+24-11k=0 | | 15y+5=23 | | K-13=56 | | 3w-2w=24-w | | 987*445=7 | | 7a-3=3+2a | | 0.2x-2=0.52-0.7x | | 36=n | | 5b-2b+8b= | | -64=-4r | | a/10=b/3 | | 4(3x-2)=112 | | -w-3=-8w+16 | | 7w-19=5w-x | | 4y-1+8y=-4 | | y=(3-2-4) | | -5c+10=-10+4-9c | | 5+2r=2x+6 | | X/3-1/2=1/4 | | K-13=57 | | 9(x+3)-3=29-3x-5+12x | | 7w=5w+8 | | 3/8=?/24 | | 2x-4=9x-7-7x | | 8x^2+16x+5=0 | | 2(4-6)-3(1+3x)=16 | | 3x^2-17x=-6 | | y=(3-2-4)2 | | 23+4v=83 | | e^7x*e^2=e^2x+8 | | 8x+3y=48slope |